2015
DOI: 10.1097/mib.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Progression of Childhood-Onset Inflammatory Bowel Disease in Northern Stockholm County

Abstract: Patients with childhood-onset IBD were characterized by extensive colitis that was relatively stable over time and associated with a relatively low risk of complications and abdominal surgery. Our findings confirm the more extensive disease location in pediatric IBD but did not identify the proposed dynamic and aggressive nature of the childhood-onset phenotype. The association of nonmucosal healing with a complicated disease course suggests that endoscopy should guide treatment intensity in childhood-onset CD. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…[22] This contrasts to the experience from Canada, where pediatric patients were reported to be subjected to surgery in a frequency of 16.4% in a study demonstrating more surgery in low socioeconomic groups vs. high socioeconomic groups. [23] Similarly, a recent French study reports a surgery frequency of 20% after five years [24] and a report from our neighbor country Finland, where 25% were operated after five years [25] raising the question whether pediatric IBD patients display different phenotypes in different countries.…”
Section: Scandinavian Journal Of Gastroenterologymentioning
confidence: 64%
“…[22] This contrasts to the experience from Canada, where pediatric patients were reported to be subjected to surgery in a frequency of 16.4% in a study demonstrating more surgery in low socioeconomic groups vs. high socioeconomic groups. [23] Similarly, a recent French study reports a surgery frequency of 20% after five years [24] and a report from our neighbor country Finland, where 25% were operated after five years [25] raising the question whether pediatric IBD patients display different phenotypes in different countries.…”
Section: Scandinavian Journal Of Gastroenterologymentioning
confidence: 64%
“…After exclusion of duplicates, 4443 records were screened. After reviewing the title and abstract and if necessary the full publications, 41 relevant studies were retrieved for full review out of 139 full‐text articles were assessed for eligibility. Studies with no baseline endoscopic assessment, less than 13 cases or with insufficient information on patients were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of the 41 studies were abstracts and 27 were retrospective studies. Twenty‐four studies were from Europe, seven from North America, seven from Asia and one from Africa . Accrual period for these studies, reported in 38 studies of 41 ranged from 1953 to 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated 25–30% of individuals with Crohn disease are diagnosed during childhood or adolescence, with involvement most commonly affecting the distal small bowel and colon [13]. Timely diagnosis and treatment of this condition is critical because misdiagnosis or under-treatment has been associated with significant co-morbidities, including impaired growth and failure to thrive, development of disease-related complications (e.g., intra-abdominal abscess and bowel obstruction), and overall reduced health-related quality of life [47].…”
Section: Introductionmentioning
confidence: 99%